Legal Liability of Corporations on License Violating in Utilizing Coastal Border For Sustainable Tourism Development in Bali Province - Gede Agung Wirawan Nusantara; I Nyoman Putu Budiartha; I Nyoman Gede Sugiartha (Warmadewa Press, 2023)
Legal liability for corporations that violate permits for using coastal borders for sustainable tourism development in Bali Province aims to examine the effectiveness of law enforcement against violations committed by corporations in utilizing coastal border areas. This research uses empirical legal research. The problem approaches used in this research proposal are the legislative approach, case approach, sociological approach, historical approach, and comparative legal approach. A comparative legal approach is carried out by comparing legal regulations in other countries, namely Canada, Norway, and Japan which have long coastlines. The philosophical basis for regulating corporate responsibility for violating permits in utilizing coastal borderline provisions in the 2nd and 5th principles of Pancasila. The effectiveness of law enforcement against permit violations by corporations in utilizing coastal border provisions for sustainable development is ineffective considering that cases of coastal border violations have not been resolved in accordance with normative provisions. The formulation of legal liability for corporations that violate coastal border permits for sustainable development is carried out with consideration of sustainable tourism development, which requires the formulation of non-litigation resolution of coastal border permit violations, namely with a Restorative Justice model mechanism.